ANALISIS BIBLIOMETRIK PENELITIAN INKUBATOR BISNIS PADA PUBLIKASI ILMIAH TERINDEKS SCOPUS - Lukmanul Hakim (Institut Bisnis dan Teknologi Pelita Indonesia, 2020)
The business incubator was first established in the United States in 1959, then developed and spread throughout the world. In line with the growth of business incubators, academics around the world are interested in researching business incubators and publishing them in internationally reputable scientific journals. This study aims to describe the development of business incubator research published in internationally reputable scientific journals. The research method used is quantitative descriptive bibliometric analysis approach. Data sources were obtained from the Scopus database with restrictions on articles published in the last ten years. Data were analyzed with the Analyze menu on Scopus and VOSviewer software. Research findings based on bibliometric analysis: Publication of Scopus indexed business incubators in 2010 - 2019 totaling 410 articles with 947 authors, and 160 different keywords; The most publications in 2019 were 91 articles; The Journal of Technology Transfer becomes the core journal of business incubator research publications; The most prolific writers are Baskaran, A. and Schwartz, M .; Most of the research affiliations are from Universidade de São Paulo-Brazil and Universidad de Santiago de Compostela-Spain; Most contributors are United States citizens. Research conclusions: First, the development of business incubator research published in the scientific journal Scopus indexed in 2009-2019 experienced positive growth. Second, bibliometric visualization of network maps based on keywords is divided into eight clusters and network maps based on the author are divided into four clusters. Inkubator bisnis pertama kali didirikan di Amerika Serikat pada tahun 1959, kemudian berkembang dan menyebar ke seluruh dunia. Sejalan dengan pertumbuhan inkubator bisnis, para akademisi di dunia tertarik meneliti inkubator bisnis dan mempublikasikannya pada jurnal ilmiah bereputasi internasional. Penelitian ini bertujuan untuk mendeskripsikan perkembangan penelitian inkubator bisnis yang dipublikasi pada jurnal ilmiah bereputasi internasional. Metode penelitian yang digunakan adalah deskriptif kuantitatif dengan pendekatan analisis bibliometrik. Sumber data diperoleh dari database Scopus dengan pembatasan artikel yang terbit sepuluh tahun terakhir. Data dianalisis dengan menu Analyze pada Scopus dan perangkat lunak VOSviewer. Temuan penelitian berdasarkan analisis bibliometrik: Publikasi penelitian inkubator bisnis yang terindeks Scopus tahun 2010 – 2019 sebanyak sebanyak 410 artikel dengan 947 penulis, dan 160 kata kunci yang berbeda; Publikasi paling banyak pada tahun 2019 yaitu sebanyak 91 artikel; Journal Of Technology Transfer menjadi jurnal inti publikasi penelitian inkubator bisnis; Penulis terproduktif adalah Baskaran, A. dan Schwartz, M.; Afiliasi peneliti terbanyak berasal dari Universidade de Sao Paulo-Brazil dan Universidad de Santiago de Compostela-Spanyol; Kontributor terbanyak berkebangsaan Amerika Serikat. Kesimpulan penelitian : Pertama, perkembangan penelitian inkubator bisnis yang dipublikasi pada jurnal ilmiah terindeks Scopus tahun 2009-2019 mengalami pertumbuhan yang positif. Kedua, visualisasi bibliometrik peta jaringan berdasarkan kata kunci terbagi menjadi delapan klaster dan peta jaringan berdasarkan penulis terbagi menjadi empat klaster.